Observatório da Educação da PUC/SP e a formação de professores que ensinam Matemática em Comunidades de Prática - Ramos, Wanusa Rodrigues (2015)
This paper aimed to identify meaning of negotiations involving Resolution of Problems occurred in the core of the PUC/SP, consisting of academics, Basic Education teachers and student teachers, under the Program Observatory of Education (Obeduc/CAPES). We adopted as theoretical framework the concept of Communities of Practice (CoP) of Lave and Wenger (1991) and Wenger (2001). Used as instruments for data collection transcripts of audio recordings of the meetings held, the researcher's field diary and participant observation, which formed the basis for selective in representing episodes in the process of our interpretative analysis. In this way, realize that the process of knowing and learning how to work with the Resolution of Problems has been validated by the CoP as an important part of the social practice of teacher teaching mathematics. We emphasize that occurred between the negotiations: the conceptual negotiations on Resolution of Problems, trading on the differences between problem and exercise and the negotiation between teachers and students, covering dimensions of the relationship between initial training and continuing education. Moreover, we point that understanding of Resolution of Problems common to the group and that became part of the shared repertoire of CoP was being built over time, the meaning was negotiated and renegotiated in several meetings, and not was free of conflict. The results of our analysis also demonstrated that, on the one hand, beginners had a more peripheral participation, by observing and listening the comments from other group members and, on the other hand, some signed as experienced members, full participation, and their words and speeches, as forms of reification, sometimes reflected the time the CoP was. We consider contexts as the Communities of Practice constitute important formative spaces where you can build identities, negotiate and renegotiate meanings about what is relevant and derive this process learning as forms of social participation